Detection and Cooperative Communications for Deployment Sensor Networks - Benaissa, Bedr-Eddine; Lahfa, Fedoua; Naima, Khatir; Lorenzini, Giulio; İnç, Mustafa; Menni, Younes (Int Information & Engineering Technology Assoc, 2021)
In a sensor network, and more specifically with a single-hop deployment policy, sensor measurements contain a lot of redundancy either in the measurement dimensions of a single sensor, or between the measurement dimensions of different sensors due to of the spatial correlation either in the temporal dimension of the measurements. The goal is to reduce this redundancy by deploying fewer sensors, while ensuring high measurement accuracy and maximizing service life. The proposed method minimizes the complexity in terms of communication and calculation and maximizes the lifetime of the network based on an aggregation and consensus system to reduce the spatio-temporal dimension of the data captured and consequently the number of sensors deployed. The results show a visible performance compared to the standard method of transmission on the free platform of the COOJA/Contiki simulator allowing to simulate network connections of wireless sensors and to interact with them.
Keywords: Wireless Sensor Network (WSN); clustering; Received Signal Strength Indicator (RSSI); IoT routing protocol